2017
DOI: 10.1002/ijc.30783
|View full text |Cite
|
Sign up to set email alerts
|

Role of quantitative p16INK4A mRNA assay and digital reading of p16INK4A immunostained sections in diagnosis of cervical intraepithelial neoplasia

Abstract: Visual interpretation of cervical biopsies is subjective and variable, generally showing fair to moderate inter‐reader agreement in distinguishing high from low grade cervical intraepithelial neoplasia (CIN). We investigated the performance of two objective p16 quantitative tests in comparison with visual assessment: (i) p16‐mRNA assay and (ii) digital analysis of sections stained for p16 protein. The primary analysis considered 232 high‐risk human papilloma virus positive (HPV+) samples from diagnostic cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Furthermore, we measured expression levels of P16, which has been reported to participate in cell cycle regulation and is now used for the clinical detection of HSIL in cervical cancer patients. [30][31][32][33][34] We found that LRP11 expression correlated with cancer differentiation and could be used as a prognostic marker, an advantage over P16 measurement. Consistent with our results, Hoang's study also found that osteosarcoma patients with positive LRP5 expression showed a trend on decreased of event-free survival.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, we measured expression levels of P16, which has been reported to participate in cell cycle regulation and is now used for the clinical detection of HSIL in cervical cancer patients. [30][31][32][33][34] We found that LRP11 expression correlated with cancer differentiation and could be used as a prognostic marker, an advantage over P16 measurement. Consistent with our results, Hoang's study also found that osteosarcoma patients with positive LRP5 expression showed a trend on decreased of event-free survival.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, to verify the results of the bioinformation analysis, we performed Western blots and IHC, and the results were consistent. Furthermore, we measured expression levels of P16, which has been reported to participate in cell cycle regulation and is now used for the clinical detection of HSIL in cervical cancer patients 3034. We found that LRP11 expression correlated with cancer differentiation and could be used as a prognostic marker, an advantage over P16 measurement.…”
Section: Discussionmentioning
confidence: 94%
“…These procedures were repeated 5 times and then we dried the plate ( 6 ). Enzyme loading: we added 50 µL of enzyme conjugate to each well, excluding the blank wells ( 7 ). Incubation: the same as step 3 ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…The available studies suggest that 75% of sexually active women will have at least one HR-HPV infection in their lifetime, of which 90% are transient and only 10% of patients develop a persistent infection. Approximately 5% of persistent infections will also progress to CIN ( 4 - 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant clinical use of immunoassays in cervical cancer diagnostics is based on IHC, where antibodies are used to visualize specific proteins on cells or tissues followed by their microscopic analysis. IHC staining of p16, an inhibitor of cyclin-dependent kinases, and Ki-67, a cell proliferation marker, showed potential for improving diagnostic accuracy [41,42]. The p16/Ki-67 dual staining technology is more sensitive than cytology in detecting CIN2+ in hrHPV-positive women and can be used for triage after a positive hrHPV test to guide the decision on how to follow-up, for example, by colposcopy [43,44].…”
Section: Immunoassaysmentioning
confidence: 99%